Assistance in writing scientific articles for teachers - Khoirul Anwar; Slamet Asari (Universitas Muhammadiyah Magelang, 2022)
Writing scientific papers for junior high school teachers is very necessary, especially how to compose the introduction, review, theory, results and discussion, and conclusions in an easy and applicable way. This activity uses two complementary mentoring methods, namely workshops and assistancing for 15 teachers from four schools in Gresik and Lamongan Regencies. The result of the program shows encouraging and positive gains. 81.8% of participants had a positive perception of the domains of preliminary preparation, theory review, presentation of results, discussion, and conclusion. The result of the interview confirms that the introduction and presentation of the results are parts that are easy to master. However, the review of theory and research methods are difficult part to master. This is because teachers often experience difficulties in integrating theoretical thinking into practical thinking. This assistance seeks to help teachers solve learning problems through a combination of theoretical and practical, and written communication skills in the form of scientific articles.